Pengembangan Sistem E-Commerce untuk Meningkatkan Penjualan Oleh-Oleh Makanan Ringan di Kabupaten Padang Pariaman - Cahyani, Yola Indra; Annas, Firdaus; Atikah, Nur (JOVISHE : Journal of Visionary Sharia Economy, 2023)
In this digital era, the use of technology as a promotional media to reach a wider market for micro, small and medium enterprises (MSMEs) to remain competitive in the national and global arenas. Padang Pariaman Regency is one of the tourist destinations rich in culture and culinary specialties. One of its culinary specialties is snack souvenirs, such as sanjai, ladu, sala lauak, and others. However, this opportunity has not been fully utilized due to the lack of knowledge about online promotional media and access to digital marketing technology. And the local community still relies on conventional marketing methods, by selling to markets, neighbors and other conventional methods. This article aims to develop a web system that can later help as a promotional media for a home industry center for snack souvenirs using a Content Management System (CMS) through an e-shop, namely openchart, which is very practical and can be used by the general public. This study uses the Research and Development (R&D) method using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The results of this study will later create a web-based promotional media, where researchers will use the OpenChart CMS. This application can be used validly, practically, efficiently, and effectively. The findings obtained from this study showed that the application of webbased promotional media, namely openchart, can help as a supporting media in informing and promoting to the wider community and can increase sales and competitiveness in Home Industry products in Padang Pariaman Regency.